2005
DOI: 10.1021/ma050308g
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Electrospinning of Cross-Linked Poly(2-hydroxyethyl methacrylate) Nanofibers and Elastic Properties of Individual Hydrogel Nanofibers in Aqueous Solutions

Abstract: Elastomeric nanofibers composed of cross-linked poly(2-hydroxyethyl methacrylate) are synthesized via a reactive electrospinning process. In this process, the photoinduced polymerization and cross-linking of polymers take place simultaneously during the electrospinning process. The produced nanofibers are mostly within the diameter range of 100-500 nm in the dry state. When they are immersed in aqueous solution, the nanofibers exhibit remarkably large elastic properties characteristic of bulk hydrogel material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 22 publications
0
75
0
1
Order By: Relevance
“…ions and chemicals from a surrounding solution to enzymes and cells embedded within the hydrogel. 22 …”
Section: Stimuli-responsive Electrospun Fibersmentioning
confidence: 99%
“…ions and chemicals from a surrounding solution to enzymes and cells embedded within the hydrogel. 22 …”
Section: Stimuli-responsive Electrospun Fibersmentioning
confidence: 99%
“…[64][65][66] Further, methacrylate-based copolymers have been electrospun to form nanofibrous coatings that can be crosslinked after formation. 67,68 We have recently reported on the electrospinning of several elements of a library of 120 poly(b-aminoester)s that were photo polymerized after formation 69 as well as novel photocrosslinkable and hydrolytically degradable elastomers. 70 Clearly, there exists a wide range of polymers that can be processed into the nanofibrous format.…”
Section: Figmentioning
confidence: 99%
“…For example, Kim and colleagues showed that cross-linked poly-HEMA nanofibers snap back into place after being distended with an AFM probe tip. 68 Tan and coworkers fixed one end of a nanofiber, and used the AFM cantilever to deform and measure force generated in PEO nanofibers. 100 Similarly, the AFM probe tip has been used to carry out three-point bending tests of individual fibers placed over a groove microetched into a silicon wafer.…”
Section: Single-fiber Mechanicsmentioning
confidence: 99%
“…Also, the nonvolatile nature of the cross-linking agent prevents the use of the vapor-phase crosslinking method (29)(30)(31). Several studies have described various other methods of creating cross-linked fibers; such as using heat (32)(33)(34)(35)(36) or UV radiation (20,(37)(38)(39) to initiate the cross-linking reaction during or after the synthesis of the fibers. Heat and UV light, however, have known microbicidal properties and thus are not suitable for use in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to make nano-and microfibers from water-soluble polymers by electrospinning offers a way to create hydrogels with nano-and microstructures. If these mechanical and biocompatible properties are combined with the high surface-to-volume ratios of fibers, the hydrogel can be used as an efficient support material both for enzymes and for immobilization of microorganisms (20). Lee and Belcher (21), Salalha et al (22), and Gensheimer et al (23) had investigated electrospinning as a possible method of encapsulating both bacteria and bacterial viruses.…”
mentioning
confidence: 99%